HUBUNGAN MOTIVASI ORANG TUA DENGAN PENGALAMAN KARIES GIGI PADA ANAK TUNAGRAHITA RINGAN DI SLB YAYASAN BAHAGIA KOTA TASIKMALAYA - Pratiwi, Kandia; Suharja, Eliati Sri; Fratiwi, WInda (Jurnal Ilmiah Keperawatan Gigi, 2024)
Background : Based on the results of Basic Health Research in 2018, the global incidence of dental and oral health problems reached 76%. The data obtained shows that the national prevalence rate for dental and oral health problems is 25.9%. The 15-24 year age group has 51.9% dental and oral health problems. This high figure is caused by a lack of individual motivation to carry out routine dental care which can be seen from the percentage of the population receiving dental care by medical personnel of only 8.7%, the largest proportion of dental problems in Indonesia is cavities/sick teeth at 45%. Objective: To determine the relationship between parental motivation and dental experience in mildly mentally retarded children at the Bahagia Foundation Special School, Tasikmalaya City. Method: This study used a cross sectional design, a population of 192 consisting of 96 parents and 96 mentally retarded children, with sampling using purposive sampling. Measuring tools use motivation questionnaires and DMF-T examination sheets. The data analysis technique uses the Spearman rank test. Results: The statistical test obtained an r value of 0.699, which means there is a strong relationship. Conclusion: There is a relationship between parental motivation and dental experience in mildly mentally retarded children at SLB Bahagia Tasikmalaya City.